EMOTICOM: A Neuropsychological Test Battery to Evaluate Emotion, Motivation, Impulsivity, and Social Cognition - Bland, Amy R.; Roiser, Jonathan P.; Mehta, Mitul A.; Schei, Thea; Boland, Heather; Campbell-Meiklejohn, Daniel K.; Emsley, Richard A.; Munafo, Marcus R.; Penton-Voak, Ian S.; Seara-Cardoso, Ana; Viding, Essi; Voon, Valerie; et al. (Frontiers in Behavioral Neuroscience, 2016)
In mental health practice, both pharmacological and non-pharmacological treatments are aimed at improving neuropsychological symptoms, including cognitive and emotional impairments. However, at present there is no established neuropsychological test battery that comprehensively covers multiple affective domains relevant in a range of disorders. Our objective was to generate a standardised test battery, comprised of existing, adapted and novel tasks, to assess four core domains of affective cognition (emotion processing, motivation, impulsivity and social cognition) in order to facilitate and enhance treatment development and evaluation in a broad range of neuropsychiatric disorders. The battery was administered to two hundred participants aged 18-50 years (50% female), 42 of whom were retested in order to assess reliability. An exploratory factor analysis identified eleven factors with eigenvalues greater than 1, which accounted for over 70% of the variance. Tasks showed moderate to excellent test-retest reliability and were not strongly correlated with demographic factors such as age or IQ. The EMOTICOM test battery is therefore a promising tool for the assessment of affective cognitive function in a range of contexts.